Impaired blood‐brain barrier in the microbiota‐gut‐brain axis: Potential role of bipolar susceptibility gene TRANK1. Issue 14 (20th May 2021) - Lai, Jianbo; Jiang, Jiajun; Zhang, Peifen; Xi, Caixi; Wu, Lingling; Gao, Xingle; Fu, Yaoyang; Zhang, Danhua; Chen, Yiqing; Huang, Huimin; Zhu, Yiyi; Hu, Shaohua
Abstract: Bipolar disorder (BD) is a common psychiatric illness with high prevalence and disease burden. Accumulating susceptibility genes for BD have been identified in recent years. However, the exact functions of these genes remain largely unknown. Despite its high heritability, gene and environment interaction is commonly accepted as the major contributing factor to BD pathogenesis. Intestine microbiota is increasingly recognized as a critical environmental factor for human health and diseases via the microbiota‐gut‐brain axis. BD individuals showed altered diversity and compositions in the commensal microbiota. In addition to pro‐inflammatory factors, such as interleukin‐6 and tumour necrosis factor‐α, type 1 interferon signalling pathway is also modulated by specific intestinal bacterial strains. Disruption of the microbiota‐gut‐brain axis contributes to peripheral and central nervous system inflammation, which accounts for the BD aetiology. Administration of type 1 interferon can induce the expression of TRANK1, which is associated with elevated circulating biomarkers of the impaired blood‐brain barrier in BD patients. In this review, we focus on the influence of intestine microbiota on the expression of bipolar gene TRANK1 and propose that intestine microbiota‐dependent type 1 interferon signalling is sufficient to induce the over‐expression of TRANK1, consequently causing the compromise of BBB integrity and facilitating the entrance of inflammatory mediators into the brain. Activated neuroinflammation eventually contributes to the occurrence and development of BD. This review provides a new perspective on how gut microbiota participate in the pathogenesis of BD. Future studies are needed to validate these assumptions and develop new treatment targets for BD.